Molecular epidemiology of lung cancer - Christiani, David (Henry Stewart Talks, 2022)
Lung cancer in the world, Smoking, Secondhand smoke, International Lung Cancer Consortium (ILCCO), Air pollution, Radon, Asbestos, Genetics of lung cancer